King Saul in the historiography of Judah. - Edelman, Diana Vikander (Library of Hebrew Bible/Old Testament studies., 1991)
A sustained close reading of 1 Samuel 8 to 2 Samuel 1 from the perspective of the intended ancient audience. A conscious effort is made here to read and understand the text ''through the eyes of an ancient Israelite'', to the extent that the world-view and idioms of late seventh-century Judah can be reconstructed. The study reveals a coherent, carefully developed narrative of Saul''s career as the first king of Israel.